Salt reduction in the world - intervention strategies and measures: a progress review - Fang FAN; Ying-hua LI (Editorial Office of Chinese Journal of Public Health, 2022)
Non-communicable diseases (NCDs) is the main cause of deaths around the world and salt reduction is considered as one of the most cost-effective priority actions to reduce the risk of NCDs. In order to reduce salt intake among residents, many countries in the world have implemented a series of salt reduction strategies and measures, such as establishing salt reduction policies, enhancing consumer health education, improving food formulations in the food industry, and implementing front-of-package labeling programs. This paper summarizes researches on source of salt, salt and health, as well as the strategies, measures and achievements of salt reduction intervention in some countries and regions, in order to provide references for carrying out relevant salt reduction actions in China.